A Netnographic Study Of The Song "One Month" On Sharing Behavior On Tiktok @Bearnotber - Herawati, Ike; Octaviani , Vethy; SM, Anis Endang (Journal of Multidisciplinary Research, 2025)
This study aims to analyze sharing behavior on TikTok social media related to Bernadya's song “Satu Bulan” using the netnography method. Data was collected through observation of comments on the TikTok account @bearnotber. This study categorized comments into several types, namely personal experiences, appreciation of the song, humor, advice and support, and emotional resonance. The results showed that many listeners felt an emotional connection with the song's lyrics, which encouraged them to share personal stories and provide mutual support. These interactions created a supportive community, strengthened social bonds among listeners, and contributed to their mental well-being. The song “Satu Bulan” serves not only as entertainment but also as a medium for coping with difficult feelings and building deeper social relationships. These findings underscore the importance of music in facilitating emotional communication and creating a safe space for individuals to share experiences and support on digital platforms. This study is expected to provide further insights into the impact of music on social behavior and mental health in the digital age.